GDF15 is associated with hepatocellular senescence and correlates with mortality in patients with alcohol-associated hepatitis - Teresa Rubio-Tomás; David Martí-Aguado; Delia Blaya; Silvia Ariño; Beatriz Aguilar-Bravo; Raquel A. Martínez García de la Torre; Marc Miravet-Marti; Raquel Ferrer-Lorente; Laura Zanatto; Zengqing Xu; Laura Garcia-Tercero; Carlos Mateos-Sánchez; et al. (JHEP Reports)
Background & Aims: Cellular senescence is characterized by the loss of proliferative capacity, cell cycle arrest, and the acquisition of a proinflammatory senescence-associated secretory phenotype (SASP). Senescence is frequently present in advanced chronic liver diseases; however, the impact of hepatocellular senescence in alcohol-associated liver disease (ALD) progression and alcohol-associated hepatitis (AH) is poorly understood. Methods: Senescence was evaluated in transcriptomic data from patients at different ALD stages: advanced fibrosis (n = 10), cirrhosis (n = 10), and AH (n = 29). Plasma GDF15 levels were tested in patients with AH (n = 68), compensated cirrhosis (n = 15), heavy drinkers without liver disease (n = 15), and healthy controls (n = 10). Results were confirmed in an independent validation cohort. Results: Transcriptomic analysis revealed an increased expression of senescence-associated genes and an enrichment of SASP gene signatures in patients with cirrhosis and particularly with AH. The association of senescence with AH was confirmed by p21 staining and the expression of senescence markers (i.e. CDKN1A, CDKN2A, CDKN2B, IL6, and SERPINE1), which positively correlated with clinical severity scores. Among the SASP factors, GDF15 was expressed in the hepatocytes of patients with AH and was strongly associated with senescence markers. Circulating GDF15 levels were specifically increased in patients with AH and positively correlated with severity scores. Moreover, plasma GDF15 levels predicted the response to corticosteroids and 90-day mortality in two independent cohorts of patients with AH. Conclusions: These results suggest that AH is characterized by the presence of hepatocellular senescence and elevated circulating levels of SASP factors, particularly GDF15, which correlates with patients’ poor outcomes. This suggests that senescence may be both a player in AH pathogenesis and a potential biomarker for AH. Impact and implications: The pathogenesis of alcohol-associated liver disease (ALD) and hepatitis (AH) remains to be fully elucidated, and there is a need for biomarkers that can effectively monitor disease progression and assess patient response to therapy. In this study, we show the association of AH with hepatocellular senescence and the hepatic expression of senescence-associated secretory phenotype (SASP) factors, which correlate with poor patient outcome. Furthermore, we provide evidence that SASP factors such as GDF15 may be potential plasma biomarkers for AH. The findings of this study lay the groundwork for future research into the role of senescence in the pathogenesis of AH, as well as into the potential use of senescence and SASP-related molecules as biomarkers for AH.